Cost consciousness: conceptual development from a management accounting perspective - Velasquez, Santiago; Suomala, Petri; Järvenpää, Marko (Qualitative research in accounting and management, 2015)
Purpose – This paper aims to take note of the need to better understand cost consciousness from a management accounting perspective and serves as an exploratory study striving to analyze how the notion has been addressed by management accounting scholars. Design/methodology/approach – This paper presents the findings of a thorough literature review identifying the drivers, interpretations, definitions and results which management accounting scholars have associated with cost consciousness. Findings – This paper has synthesized the definitions and interpretations by considering their conceptual broadness and the subjects that cost consciousness characterizes. In addition, various potential drivers of cost consciousness have been identified where management control systems play a major role. Also, this paper summarizes both the positive and negative outcomes which scholars seem to expect from an increase of cost consciousness. Research limitations/implications – Given that no prior work has focused on the conceptual development of cost consciousness, it was necessary to infer most of the interpretations, drivers and results which management accounting scholars have associated to the cost consciousness notion. Originality/value – Cost consciousness is a concept that appears in hundreds of peer-reviewed articles on management accounting. However, only a handful of management accounting scholars have defined or evaluated this concept to a certain degree. As a result, what management accountants believe cost consciousness to be, how it is driven and what result may be expected from it, is nowhere to be found in any synthesized manner. The findings of this paper develop the concept of cost consciousness by illuminating the common use of the construct across various disciplines.